2017
DOI: 10.1038/s41559-016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test and refutation of a classic case of molecular adaptation in Drosophila melanogaster

Abstract: Identifying the genetic basis for adaptive differences between species requires explicit tests of historical hypotheses concerning the effects of past changes in gene sequence on molecular function, organismal phenotype and fitness. We address this challenge by combining ancestral protein reconstruction with biochemical experiments and physiological analysis of transgenic animals that carry ancestral genes. We tested a widely held hypothesis of molecular adaptationthat changes in the alcohol dehydrogenase prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…An alternative hypothesis for negative experimental results on such candidates is that they are population genetic false positives or that the appropriate phenotypes have not been measured. The positive experimental results reported here are cause for a somewhat more optimistic view, in support of other similar work on Drosophila (Laurie-Ahlberg and Stam 1987, Catalán et al 2016, Siddiq et al 2017, Glaser-Schmitt and Parsch 2018, Yang and Edery 2018). We compared two genotypes that differed for a single amino acid variant and found that four of six assayed phenotypes were different: embryo UV sensitivity, embryo hatch rates, chill coma recovery, and starvation resistance (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…An alternative hypothesis for negative experimental results on such candidates is that they are population genetic false positives or that the appropriate phenotypes have not been measured. The positive experimental results reported here are cause for a somewhat more optimistic view, in support of other similar work on Drosophila (Laurie-Ahlberg and Stam 1987, Catalán et al 2016, Siddiq et al 2017, Glaser-Schmitt and Parsch 2018, Yang and Edery 2018). We compared two genotypes that differed for a single amino acid variant and found that four of six assayed phenotypes were different: embryo UV sensitivity, embryo hatch rates, chill coma recovery, and starvation resistance (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…ASR is now widely used in evolutionary molecular biology and biochemistry ( Bridgham et al, 2009 ; Natarajan et al, 2013 ; Ortlund et al, 2007 ; Anderson et al, 2016 ; Bridgham et al, 2006 ; Finnigan et al, 2012 ; Hart et al, 2014 ; Howard et al, 2014 ; McKeown et al, 2014 ; Nguyen et al, 2016 ) and has been used to study the evolution of transcriptional networks in microbes ( Sorrells et al, 2015 ; Baker et al, 2012 ; Baker et al, 2013 ). Recently, transgenic animals carrying reconstructed ancestral genes have been engineered to test the effects of historical genetic changes on physiology and fitness ( Siddiq et al, 2017a ), but this approach has not yet been applied to the study of development.…”
Section: Introductionmentioning
confidence: 99%
“…Although adaptation genomics can in principle quite readily identify such candidate polymorphisms, a major—but rarely accomplished—objective is to experimentally validate these candidates as genic targets of selection (Barrett and Hoekstra ; Turner ; Flatt ; Siddiq et al. ). Thus, with a few exceptions, examples of causative life‐history variants remain rare (Schmidt et al.…”
mentioning
confidence: 99%